Causal relationship on volatility prices of coal-based enterprise and exchange rate (Asian Journal of Economics and Business Management, 2022)
Stock prices movement of coal company is possible to be a reflection of its business performance that allow investors' decisions to invest. The study is aimed to examine the dynamic relationship of Indonesian coal sub-sector company and exchange rate. The novelty of this study is to examined the coal based-company stock prices dynamically to exchange rate. The method in this study used Vector Autoregressive (VAR) model. The results showed that the VAR(5) model was the best model in testing the causal relationship between PTBA stock price and the exchange rate. The VAR(5) model is also used to forecast data for the next 30 days. For further study, it suggested to extend the variables to some other macroeconomics indicators.